Déterminants Psycho-Socio-Culturels De La Victimisation Des Employées Mineures De Ménages À Abidjan - Okpo, Par Nassoua Antoine (European Scientific Journal, ESJ, 2017)
This study aims to identify the psycho-sociocultural determinants of the victimization of minors employed by households. Two hypotheses have led to this research. Semi-directional interviews with parents and employers of minors were used. Three theories have been convened; The culturalist theory of the cultural transmission of values and beliefs, the theory of reasoned action and that of planned action have led to knowledge of the motivations of employers. The consciousness of the tacit guarantee of the impunity of the person who chastises a minor, the acceptance of punishments as a deterrent and educational force during socialization, and the subjective interpretation of the actions of minors are the main psychosociocultural determinants Of the victimization of minors. These motivate and trigger the victim's attitude in the employer.